Technical efficiency of tank mixtures of herbicides in crops of winter wheat after non–steam predecessors in the conditions of the Northern Steppe of Ukraine - V. Matyukha (Карантин і захист рослин)
Goal. To establish the biological effectiveness of herbicides and their tank mixtures for the protection of winter wheat crops from weeds in the Steppe of Ukraine.